Micro-space intelligent shaping solid drying agent and preparation method thereof

Through the combination of materials with specific ratios and injection molding technology, a micro-space intelligent shaping solid desiccant was developed, which solved the problem of limited application of existing desiccants in small spaces, achieved efficient hygroscopy and plasticity, and was suitable for high-tech products and micro-medical devices and other fields.

CN119633780AActive Publication Date: 2025-03-18SUPER DRY DESICCANT SHENZHEN
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510141403.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-18
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The existing desiccants are limited in applications in small spaces, and there are problems of dust pollution and size impairment, making it difficult to meet the humidity control needs in fields such as high-tech products and micro medical devices.

Method used

A micro-space intelligent shaping solid desiccant is developed to prepare high-performance desiccants with custom shapes and sizes through the combination of plastic particles, inorganic particles and activated carbon with specific ratios.

Benefits of technology

This desiccant not only has efficient moisture absorption performance, but also has excellent plasticity and stability. It can meet the different needs of small spaces from small to several millimeters to larger-sized equipment. It is suitable for high-tech products and micro medical devices and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of desiccant preparation, and particularly relates to a micro-space intelligent shaping solid desiccant and a preparation method thereof. The micro-space intelligent shaping solid drying agent is prepared from the following raw materials in percentage by weight: 20%-35% of plastic particles, 15%-20% of silicon dioxide, 20%-35% of calcium carbonate and 20%-38% of sodium aluminosilicate. The PP plastic particles, the ABS plastic particles, the silicon dioxide, the calcium carbonate and the sodium aluminosilicate are mixed according to a certain proportion, and the high-performance drying agent with customizable shape, size and thickness is prepared by utilizing an injection molding technology. The drying agent not only has excellent moisture absorption performance, but also is smooth in surface, does not need secondary packaging, and can be directly applied to various tiny spaces needing humidity control or used as components of products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of desiccant preparation, and in particular relates to a micro-space intelligent shaping solid desiccant and a preparation method thereof. Background Art

[0002] In many fields such as electronic products (such as electric toothbrushes), precision instruments (mobile phones), food and drug packaging, and cultural relics preservation, the control requirements for micro-environment humidity are extremely high, especially in occasions where space is extremely limited. The application of traditional desiccants is severely restricted. The mainstream types of desiccants on the market currently include calcium chloride desiccants, silica gel desiccants, magnesium chloride desiccants, molecular sieve desiccants, calcium oxide desiccants, and montmorillonite desiccants. Although these desiccants have their own characteristics, they generally have two common problems in their application.

[0003] 1. Dust problem: All the desiccants mentioned above, whether based on chemical reaction moisture absorption (such as calcium chloride, calcium oxide) or physical adsorption (such as silica gel, molecular sieve), are prone to dust from their raw materials themselves or during their use. Dust not only pollutes the protected items, but may also pose a threat to human health, especially when used in closed or small spaces. Therefore, these desiccants usually require additional secondary packaging in actual applications, that is, the desiccant raw materials are sealed and wrapped with packaging film to prevent dust from leaking out. This not only increases production costs, but also limits the application of desiccants in certain occasions where there are strict requirements on packaging volume and weight.

[0004] 2. Size and shape limitations: Existing desiccant products are usually large in size (length or diameter greater than 1 cm) and thicker than 2 mm. Such size and thickness make it difficult for them to meet the humidity control needs of tiny spaces (such as tiny gaps inside electronic devices, micro sensor packaging, etc.). This size limitation seriously hinders the widespread application of desiccant in high-tech products, micro medical devices and other fields, and cannot meet the requirements of modern industry for miniaturization and integration.

[0005] In precision electronic devices such as electric toothbrushes, desiccants not only need to have efficient moisture absorption capacity, but also need to take into account structural strength, wear resistance, chemical stability, and the ability to adapt to narrow spaces. Therefore, in order to overcome the above defects, it is necessary to develop a micro-space intelligent shaping solid desiccant that can be flexibly made into a variety of shapes according to the specific needs of the space to be dried, and can even be directly integrated into and become a component of the customer's product, thereby greatly broadening the application range of the desiccant. Summary of the invention

[0006] The object of the present invention is to provide a micro-space intelligent shaping solid desiccant and a preparation method thereof, wherein the micro-space intelligent shaping solid desiccant has excellent plasticity while maintaining high-efficiency moisture absorption performance.

[0007] A micro-space intelligent shaping solid desiccant, whose preparation raw materials are, by weight percentage, 20%-35% plastic particles, 15%-20% silicon dioxide, 20%-35% calcium carbonate, and 20%-38% sodium aluminosilicate.

[0008] In some preferred schemes, the micro-space intelligent shaping solid desiccant is prepared from the following raw materials, calculated by weight percentage: 25%-30% plastic particles, 17%-19% silicon dioxide, 20%-28% calcium carbonate, and 20%-30% sodium aluminosilicate.

[0009] In some preferred schemes, the micro-space intelligent shaping solid desiccant also includes activated carbon and dye, and the added amounts of the activated carbon and dye are 10%-15% and 0.1%-0.5% of the mass of the micro-space intelligent shaping solid desiccant, respectively.

[0010] The plastic particles include PP and ABS.

[0011] The mass ratio of PP to ABS is 1:(0.5-2); more preferably, it is 1:1.

[0012] The PP is homopolymer PP, with a melt index of 8-13 g / 10 min at 230°C and a density of 0.89-0.92 g / cm 3 , tensile yield stress ≥33MPa.

[0013] The PP was purchased from ExxonMobil, PP1304E5.

[0014] The ABS has a melt index of 2-3 g / 10 min at 220°C and a density of 1.03-1.07 g / cm 3 , 1 / 4" IZOD impact strength ≥ 6.5ft·lb / in.

[0015] The PP was purchased from Chi Mei, Taiwan, China, PA-747R.

[0016] Selecting specific PP plastic particles as the base carrier of the desiccant and blending them with specific ABS plastic particles can improve the structural strength of the desiccant while maintaining its hygroscopic properties, thereby ensuring its integrity. This may be due to the synergistic effect between the two plastic particles. PP plastic particles provide a solid foundation for the desiccant with its light weight, high rigidity and good processing properties. Its density is between 0.89g / cm³ and 0.92g / cm³, ensuring that the desiccant inside the electric toothbrush will not be too heavy to affect the overall weight, while maintaining sufficient structural support. In addition, PP plastic particles have stable chemical properties, which means that it will not react adversely with other materials in the complex environment of the electric toothbrush, thereby ensuring the long-term effectiveness and safety of the desiccant. The addition of ABS plastic particles further enhances the structural strength of the desiccant, and can significantly enhance the overall toughness of the desiccant after blending with PP plastic particles. This enhancement is crucial for the internal components of the electric toothbrush, because the electric toothbrush will experience frequent vibration and friction during use, and the desiccant needs to maintain its integrity and hygroscopic properties to continuously protect the inside of the electric toothbrush from moisture. Therefore, the high rigidity of PP plastic particles provides a stable structural framework for the desiccant, while the high impact strength and wear resistance of ABS plastic particles enhance the toughness of this framework. The synergistic effect of the two enables the desiccant to maintain a stable structural form inside the electric toothbrush while resisting the impact from vibration and friction, thereby ensuring the long-term stability and reliability of the electric toothbrush and enabling the desiccant to continue to play its hygroscopic and protective role in complex environments. However, the amount of plastic particles added should not be too high. When the total amount of plastic particles exceeds 35%, on the one hand, since PP and ABS plastic particles themselves do not have hygroscopic function, their excessive addition will occupy the space inside the desiccant, thereby reducing the proportion of effective hygroscopic components (such as fumed silica and sodium aluminosilicate), resulting in a significant decrease in the hygroscopic capacity of the desiccant. On the other hand, the cost of plastic particles is relatively high, and excessive addition will increase the production cost of the desiccant and reduce its market competitiveness.

[0017] In some preferred solutions, the ABS may also be made of other wear-resistant materials that can be injection molded, such as polyamide plastics.

[0018] The silicon dioxide is fumed silicon dioxide with a particle size of 300-400 meshes.

[0019] The fumed silica was purchased from Shandong Kasong New Materials Co., Ltd.

[0020] The particle size of the calcium carbonate is 100-150 meshes.

[0021] The calcium carbonate was purchased from Shijiazhuang Hualang Mineral Products Trading Co., Ltd.

[0022] The particle size of the sodium aluminosilicate is 150-250 meshes.

[0023] The sodium aluminosilicate was purchased from Guangdong Ousman Biotechnology Co., Ltd.

[0024] The selection of three inorganic particles with different particle sizes can not only improve the moisture absorption effect of the desiccant, but also improve the moisture absorption stability. This may be because the three inorganic particles have a synergistic effect. Fumed silica and sodium aluminosilicate jointly improve the moisture absorption efficiency of the desiccant, allowing the desiccant to absorb and lock moisture more quickly, while maintaining a dry environment inside the electric toothbrush to help the desiccant maintain stable moisture absorption performance for a long time, effectively preventing moisture from corroding electronic components. Fumed silica also enhances the structural stability of the desiccant, allowing it to maintain stable moisture absorption performance and not deform under harsh conditions such as high temperature and high humidity. At the same time, the filling effect of calcium carbonate further improves the physical strength of the desiccant. Moreover, as a filler, calcium carbonate not only adjusts the hardness of the desiccant, allowing it to better fit the internal components of the electric toothbrush, but also reduces production costs and improves the economy of the desiccant. In addition, the selected inorganic particles have different particle sizes, which can further improve the strength and toughness of the desiccant. The three inorganic particles with different particle sizes can form a particle size complementary effect in the plastic particle matrix. Larger nanoparticles can act as stress concentration points to induce silver cracks or cavitation effects, while smaller nanoparticles can fill these defects and terminate the propagation of cracks. This complementary particle size effect helps to form a denser toughening network and improve the overall performance of the desiccant.

[0025] However, the amount of silica and calcium carbonate added should not be too large. Due to the low density of fumed silica and the strong interaction between particles, when the amount of fumed silica added exceeds 20%, not only will the desiccant mixture be difficult to compact during the molding process and unable to form a stable structure, but it will also make the desiccant more easily broken when subjected to external forces, reducing its service life and performance stability. When the amount of calcium carbonate added exceeds 35%, similar to fumed silica, not only will the desiccant mixture be difficult to compact during the molding process and unable to form a stable structure, but it will also reduce the toughness of the desiccant, making it more easily broken when subjected to external forces. In addition, although calcium carbonate itself has a certain hygroscopic capacity, its effect is far less than that of high-efficiency hygroscopic materials such as fumed silica and sodium aluminosilicate. Therefore, excessive addition of calcium carbonate will further reduce the hygroscopic properties of the desiccant.

[0026] In some preferred embodiments, the fumed silica can be replaced by other nanomaterials having hygroscopic properties, such as nano-alumina, nano-calcium oxide, and the like.

[0027] The activated carbon is coal-based activated carbon with a particle size of 8-20 meshes and a phenol adsorption capacity of ≥160 mg / g.

[0028] In some preferred embodiments, the activated carbon is purchased from Zhejiang Zhelang Activated Carbon Co., Ltd.

[0029] The dye is commercially available and is not specifically limited in the present invention.

[0030] The preparation method of the micro-space intelligent shaping solid desiccant comprises the following steps: S1. Desiccant mixing: put all raw materials into the reactor according to the proportion, set the speed to 55-65r / min, stir at 215-225℃, and adjust the speed to 195-205r / min and continue stirring after the plastic particles are completely melted. The stirring time is ≥30min; S2. Adjust the temperature to 215-225°C, the speed to 115-125r / min, open the outlet valve to maintain the reactor at standard atmospheric pressure, then open the inlet valve at the bottom of the reactor, and slowly introduce carbon dioxide gas into the reactor for 30-60 minutes; S3. The uniformly molten material is sent from the reactor into the hopper of the screw extruder. The size of the desiccant is customized by the die of the extruder. The material is extruded, granulated, cooled, dehydrated and dried.

[0031] During the desiccant preparation process, carbon dioxide gas is slowly introduced into the reactor under standard atmospheric pressure. The carbon dioxide gas forms tiny bubbles in the molten material, which helps to further evenly mix the materials and improve the microstructure of the desiccant, thereby improving the performance of the desiccant.

[0032] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention provides a micro-space intelligent shaping solid desiccant, which is prepared by mixing PP plastic particles, ABS plastic particles, fumed silica, calcium carbonate and sodium aluminosilicate in a certain proportion, and using injection molding technology to prepare a high-performance desiccant with customizable shape, size and thickness. The desiccant not only has excellent moisture absorption performance, but also has a smooth surface and does not require secondary packaging. It can be directly applied to various micro spaces that require humidity control or as a component of a product.

[0033] 2. The present invention uses a special ratio of hygroscopic materials and molding technology, so that the desiccant has excellent plasticity while maintaining efficient hygroscopic performance. By precisely controlling the molding process, the desiccant can be molded into various shapes and sizes to meet the different needs of tiny spaces as small as a few millimeters to larger-sized devices. This customization capability allows the desiccant to be seamlessly integrated into product design without the need for additional secondary packaging, which simplifies the production process and reduces costs.

[0034] 3. The desiccant of the present invention does not undergo significant changes in form or structure after absorbing moisture, keeps the surface smooth and clean, and avoids the pollution to the product or environment caused by the traditional desiccant due to moisture absorption expansion or dust generation. This feature makes the desiccant particularly suitable for application scenarios with extremely high requirements for cleanliness and stability, such as electronic products, precision instruments, food and drug packaging, etc.

[0035] 4. The present invention selects specific PP plastic particles as the basic carrier of the desiccant and blends them with specific ABS plastic particles, which can improve the structural strength of the desiccant while maintaining its hygroscopic properties, thereby ensuring its integrity.

[0036] 5. The present invention selects three inorganic particles of different particle sizes for compounding, which can not only improve the moisture absorption effect of the desiccant, but also improve the moisture absorption stability.

[0037] 6. In the desiccant preparation process of the present invention, carbon dioxide gas is slowly introduced into the reactor under standard atmospheric pressure. The carbon dioxide gas forms tiny bubbles in the molten material, which helps to further evenly mix the material and improve the microstructure of the desiccant, thereby improving the performance of the desiccant. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] PP is homopolymer PP, with a melt index of 8-13g / 10min at 230°C and a density of 0.89-0.92g / cm 3 , tensile yield stress ≥33MPa, purchased from ExxonMobil, PP1304E5.

[0040] The melt index of ABS at 220°C is 2-3g / 10min, and the density is 1.03-1.07g / cm 3 , 1 / 4" IZOD impact strength ≥ 6.5ft·lb / in, purchased from Chi Mei, Taiwan, China, PA-747R.

[0041] Fumed silica, with a particle size of 300-400 mesh, was purchased from Shandong Kasong New Materials Co., Ltd.

[0042] Calcium carbonate, with a particle size of 100-150 mesh, was purchased from Shijiazhuang Hualang Mineral Products Trading Co., Ltd.

[0043] Sodium aluminosilicate, with a particle size of 200 mesh, was purchased from Guangdong Ousman Biotechnology Co., Ltd.

[0044] Example 1 The present embodiment provides a micro-space intelligent shaping solid desiccant, and its preparation raw materials are, by weight percentage: 25% plastic particles, 19% fumed silica, 27% calcium carbonate, and 29% sodium aluminosilicate.

[0045] The plastic particles are PP and ABS, with a mass ratio of 1:1.

[0046] The preparation method of the micro-space intelligent shaping solid desiccant comprises the following steps: S1. Desiccant mixing: put all raw materials into the reactor according to the proportion, set the speed to 60r / min, stir at 220℃, and adjust the speed to 200r / min and continue stirring after the plastic particles are completely melted. The stirring time is 40min; S2. Adjust the temperature to 220°C, the speed to 120r / min, open the outlet valve to maintain the reactor at standard atmospheric pressure, then open the inlet valve at the bottom of the reactor to slowly introduce carbon dioxide gas into the reactor for 50 minutes; S3. The uniformly molten material is sent from the reactor into the hopper of the screw extruder. The size of the desiccant is customized by the die of the extruder. The material is extruded, granulated, cooled, dehydrated and dried.

[0047] Example 2 The difference between this embodiment and embodiment 1 is that the micro-space intelligent shaping solid desiccant is prepared from the following raw materials, calculated by weight percentage: 30% plastic particles, 17% fumed silica, 27% calcium carbonate, and 26% sodium aluminosilicate.

[0048] Example 3 The difference between this embodiment and embodiment 1 is that the plastic particles are PP and PA6, and the mass ratio is 1:1.

[0049] The density of PA6 is 1.08 g / cm 3 , simply supported beam notched impact strength is 80kJ / m 2 , purchased from Nanjing Delron Engineering Plastics Co., Ltd., B801.

[0050] Example 4 The difference between this embodiment and embodiment 1 is that the micro-space intelligent shaping solid desiccant is prepared from the following raw materials by weight percentage: 25% plastic particles, 19% aluminum oxide, 27% calcium carbonate, and 29% sodium aluminosilicate. The aluminum oxide has a particle size of 300-400 mesh.

[0051] Example 5 The difference between this embodiment and embodiment 1 is that the micro-space intelligent shaping solid desiccant further comprises activated carbon and dye, and the addition amount of the activated carbon and dye is 10% and 0.1% of the mass of the micro-space intelligent shaping solid desiccant, respectively. The dye is a yellow masterbatch purchased from Shanghai Xicong Plastic Products Co., Ltd.

[0052] Comparative Example 1 The difference between this comparative example and Example 1 is that the micro-space intelligent shaping solid desiccant is prepared from the following raw materials, calculated by weight percentage: 35% plastic particles, 12% fumed silica, 23% calcium carbonate, and 30% sodium aluminosilicate.

[0053] Comparative Example 2 The difference between this comparative example and Example 1 is that the micro-space intelligent shaping solid desiccant is prepared from the following raw materials, calculated by weight percentage: 15% plastic particles, 24% fumed silica, 30% calcium carbonate, and 31% sodium aluminosilicate.

[0054] Comparative Example 3 The difference between this comparative example and Example 1 is that the micro-space intelligent shaping solid desiccant is prepared from the following raw materials, calculated by weight percentage: 10% plastic particles, 26% fumed silica, 30% calcium carbonate, and 34% sodium aluminosilicate.

[0055] Comparative Example 4 The difference between this comparative example and Example 1 is that the micro-space intelligent shaping solid desiccant is prepared from the following raw materials, calculated by weight percentage: 25% plastic particles, 15% fumed silica, 40% calcium carbonate, and 20% sodium aluminosilicate.

[0056] Comparative Example 5 The difference between this comparative example and Example 1 is that the plastic particles are PP.

[0057] Comparative Example 6 The difference between this comparative example and Example 1 is that the particle size of the fumed silica is 100-200 mesh and is purchased from Shandong Kasong New Materials Co., Ltd.

[0058] Comparative Example 7 The difference between this comparative example and Example 1 is that the preparation method of the micro-space intelligent shaping solid desiccant comprises the following steps: S1. Desiccant mixing: put all raw materials into the reactor according to the proportion, set the speed to 55-65r / min, stir at 215-225℃, and adjust the speed to 195-205r / min and continue stirring after the plastic particles are completely melted. The stirring time is 60min. S2. The uniformly molten material is sent from the reactor into the hopper of the screw extruder. The size of the desiccant is customized by the die of the extruder. The material is extruded, granulated, cooled, dehydrated and dried.

[0059] Performance Testing The moisture absorption rate of the prepared desiccant after being placed at 28°C and 90%RH for 7 days was tested with reference to GB / T 41897-2022 "Quality Requirements for Desiccant for Food". The size of the desiccant was 15*12*5mm, and the state of the sample before and after moisture absorption was observed. Three parallel samples were tested for each group of samples. The results are shown in Table 1.

[0060]

[0061] According to statistics, the micro-space intelligent shaping solid desiccant prepared by Examples 1 to 5 of the present invention has a small sample size but a good molding effect, a high moisture absorption rate, and the sample remains intact after moisture absorption, indicating good moisture absorption stability. In Comparative Example 1, the amount of silicon dioxide added is too small, the amount of plastic particles added in Comparative Example 2 and Comparative Example 3 is too small, the amount of silicon dioxide added is too large, the amount of calcium carbonate added in Comparative Example 4 is excessive, the amount of silicon dioxide and sodium aluminosilicate added is too small, Comparative Example 5 does not add ABS, Comparative Example 6 has a large silicon dioxide particle size, and Comparative Example 7 does not introduce carbon dioxide gas during melting. The prepared desiccant has poor molding effect, moisture absorption effect, and moisture absorption stability. Therefore, the micro-space intelligent shaping solid desiccant prepared by the raw materials and methods described in this application not only has excellent hygroscopicity, but also has good moisture absorption stability, and can also be molded into various shapes and sizes to meet the different needs of small spaces ranging from a few millimeters to larger-sized equipment, and is particularly suitable for application scenarios with extremely high requirements for cleanliness and stability, such as electronic products, precision instruments, food and drug packaging, etc.

[0062] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A micro-space intelligent shaping solid desiccant, characterized in that: The raw materials for its preparation are: 20%-35% plastic particles, 15%-20% silicon dioxide, 20%-35% calcium carbonate, and 20%-38% sodium aluminosilicate by weight percentage; the plastic particles include PP and ABS; the PP is homopolymer PP, the melt index at 230°C is 8-13g / 10min, and the density is 0.89-0.92g / cm 3 , tensile yield stress ≥33MPa.

2. The micro-space intelligent shaping solid desiccant according to claim 1, characterized in that: The micro-space intelligent shaping solid desiccant is prepared from the following raw materials by weight: 25%-30% plastic particles, 17%-19% silicon dioxide, 20%-28% calcium carbonate, and 20%-30% sodium aluminosilicate.

3. The micro-space intelligent shaping solid desiccant according to claim 1, characterized in that: The mass ratio of PP to ABS is 1:(0.5-2).

4. The micro-space intelligent shaping solid desiccant according to claim 1, characterized in that: The silicon dioxide is fumed silicon dioxide with a particle size of 300-400 meshes.

5. The micro-space intelligent shaping solid desiccant according to claim 1, characterized in that: The calcium carbonate has an average particle size of 20 nm and a specific surface area of ​​30-60 m 2 / g.

6. The micro-space intelligent shaping solid desiccant according to claim 1, characterized in that: The particle size of the sodium aluminosilicate is 150-250 meshes.

7. The micro-space intelligent shaping solid desiccant according to claim 1, characterized in that: The ABS has a melt index of 2-3 g / 10 min at 220°C and a density of 1.03-1.07 g / cm 3 , 1 / 4" IZOD impact strength ≥ 6.5ft·lb / in.

8. A method for preparing the micro-space intelligent shaping solid desiccant according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Desiccant mixing: put all raw materials into the reactor according to the proportion, set the speed to 55-65r / min, stir at 215-225℃, and adjust the speed to 195-205r / min and continue stirring after the plastic particles are completely melted. The stirring time is ≥30min; S2. Adjust the temperature to 215-225°C, the speed to 115-125r / min, open the outlet valve to maintain the reactor at standard atmospheric pressure, then open the inlet valve at the bottom of the reactor, and slowly introduce carbon dioxide gas into the reactor for 30-60 minutes; S3. The uniformly molten material is sent from the reactor into the hopper of the screw extruder. The size of the desiccant is customized by the die of the extruder. The material is extruded, granulated, cooled, dehydrated and dried.

Citation Information

Patent Citations

  • Plastic mineral silica flaky dessicant and preparation method thereof

    CN103506067A

  • Calcium oxide-silicon dioxide composite material and preparation method thereof, liquid desiccant and preparation method and application thereof, and packaged OLED

    CN117085660A

  • Granular drying agent and preparation method thereof

    CN117339581A

  • Leakage-free solid drying agent special for electronic products and preparation method of leakage-free solid drying agent

    CN118179220A

  • Composite drying agent and preparation method thereof

    CN118437280A